2005
DOI: 10.1002/eji.200425897
|View full text |Cite
|
Sign up to set email alerts
|

Reduced p38 mitogen-activated protein kinase in donor grafts accelerates acute intestinal graft-versus-host disease in mice

Abstract: The gastrointestinal tract is a major target of graft-versus-host disease (GVHD), which constitutes a life-threatening complication of bone marrow transplantation. GVHD is mainly caused by the activation of donor-derived lymphocytes, in which cytokine cascades play essential roles. Since p38 MAPK (p38) has been identified as a regulator of cytokine reactions and proposed as a molecular target for anti-inflammatory therapy, we investigated the contribution of p38 to the severity of murine intestinal GVHD. Unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…We modified the mouse model for allogeneic BMT and DLI with a full mismatch for major histocompatibility complex class I and II (B6 [H‐2b] or BALB/c [H‐2d] into BDF1 [H‐2b/d]) to study the GVT effect against solid tumors. Our preliminary experiments demonstrated that BMT and DLI combined with 1,200 rad irradiation caused 100% mortality from GVHD within 30 days 28. On the other hand, the allogeneic DLI mice survived for at least 2 months under conditions of 950 rad.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…We modified the mouse model for allogeneic BMT and DLI with a full mismatch for major histocompatibility complex class I and II (B6 [H‐2b] or BALB/c [H‐2d] into BDF1 [H‐2b/d]) to study the GVT effect against solid tumors. Our preliminary experiments demonstrated that BMT and DLI combined with 1,200 rad irradiation caused 100% mortality from GVHD within 30 days 28. On the other hand, the allogeneic DLI mice survived for at least 2 months under conditions of 950 rad.…”
Section: Resultsmentioning
confidence: 76%
“…Our preliminary experiments demonstrated that BMT and DLI combined with 1,200 rad irradiation caused 100% mortality from GVHD within 30 days. 28 On the other hand, the allogeneic DLI mice survived for at least 2 months under conditions of 950 rad. Since systemic GVHD could be enhanced in proportion to the irradiation dose, 29 it was assumed GVHD would not be lethal with 950 rad irradiation.…”
Section: The Combination Of Irradiation and B6-derived DLI Suppressesmentioning
confidence: 99%
“…Acute GvHD: Although p38 MAPK inhibition seems promising in cGvHD, the treatment is questionable since reduced p38α MAPK levels (heterozygous p38α-KO) in donor grafts were found to accelerate acute intestinal GvHD in mice ( 197 ). Surprisingly, and contrary to the previously described cGvHD study, loss of donor p38 reinforced GvHD severity and reduced the survival of the mice.…”
Section: P38 Mitogen-activated Protein Kinase (Mapk)mentioning
confidence: 99%
“…Although p38α loss prolonged the survival of donor-derived intestinal intraepithelial lymphocytes in vitro and in vivo , donor lymphocyte expansion was decreased in the mesenteric lymph nodes upon p38α deficiency. Although the role of p38α-loss in the recipient compartment was not investigated, the study revealed a dichotomous effect of p38α in regulating inflammatory responses, cytokine expression, lymphocyte proliferation and intestinal GvHD after allo-HCT ( 197 ). Taken together with the before-mentioned study, the role of p38 MAPK in GvHD is still unclear and needs more detailed investigation, also comparing effects in chronic and acute GvHD as these could always be different ( 17 , 197 ).…”
Section: P38 Mitogen-activated Protein Kinase (Mapk)mentioning
confidence: 99%
See 1 more Smart Citation